Mochila al hombro. A way of extracurricular integral training for university students - Daniel Fernández-Urgellés; Yadislay Orphee-Faure; Alberto Planche-Morasen (Universidad de Guantánamo, 2015)
The project "Con mochila al hombro", is part of the priorities and demands of the University Extracurricular Program, its intention is to strengthen the link of the University of Guantánamo with the community, through the activities with university students, in a way that contributes to the training of subjects for their own transformation processes in an emancipating sense. It links students and professors of all faculties and University Centers of the University of Guantanamo, committed to the Cuban social project, in a competent, critical, appealing way to manage transformation processes in conjunction with the society of Guantanamo. Since its creation two years ago, it has strengthened the extracurricular work related to key areas, the quality standards for the accreditation of majors, as well as the improvement in the quality of teaching, scientific, cultural and humanistic processes of students and professors, focusing on the individual as a fundamental agent of change of his reality and of collaborative and participatory knowledge, in search of an integral training of Guantanamo university students.